Role of stainless steels in industrial heat exchangers. (Nickel Institute, 2020)
The amount of stainless steel utilized in heat exchange equipment is increasing as industry strives toward greater efficiency and reduced costly shutdowns in its operations and higher product purity. As will be shown, stainless steel is sometimes the only material that can be used; in other situations, it is the most economical when costs of installation, maintenance and production stoppages are considered. This handbook describes use of stainless steel in industrial heat exchange.
"Originally, this handbook was published in 1975 by the Committee of Stainless Steel Producers, American Iron and Steel Institute. The Nickel Institute republished the handbook in 2020."
Keywords: Heat exchangers -- Design and construction.; elektronické knihy; electronic books